A heat radiation blocking type composite gel for preventing and treating mine fire and a preparation method thereof

CN122937447APending Publication Date: 2026-10-20TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611214226.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]为了克服现有技术的不足,解决现有防灭火技术在热辐射主导的高温火区存在高温失效、难以对热辐射有效阻断等技术问题,本发明提供一种防治矿井火灾的热辐射阻断型复合凝胶及其制备方法

Benefits of technology

1、本发明选用羟丙基甲基纤维素、粉煤灰、海泡石和膨胀石墨制备的热辐射阻断型复合凝胶,羟丙基甲基纤维素分子链疏水缔合形成致密交联网络,粉煤灰颗粒填充于网络中增强覆盖层致密性与结构强度,海泡石纤维穿插于骨架中,在高温下形成交织支撑结构,维持覆盖层完整性,阻隔氧气向煤体表面扩散;膨胀石墨高温膨胀形成疏松多孔的隔热炭层,衰减热辐射向煤体的传递,实现对热辐射进行有效阻断;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to a heat radiation blocking composite gel for preventing mine fires and its preparation method, belonging to the field of inhibitor technology. It solves the technical problems of existing fire prevention and extinguishing technologies, such as high-temperature failure and difficulty in effectively blocking heat radiation in high-temperature fire zones dominated by heat radiation. The heat radiation blocking composite gel for preventing mine fires comprises, by weight, 100 parts ultrapure water, 1-2.5 parts hydroxypropyl methylcellulose, 30 parts fly ash, 0-4 parts sepiolite, and 0-4 parts expanded graphite. The preparation method is as follows: S1, preparing a hydroxypropyl methylcellulose base solution; S2, adding sepiolite to the hydroxypropyl methylcellulose base solution and stirring to disperse; S3, adding fly ash to the slurry from step S2 and stirring to disperse; S4, adding expanded graphite to the slurry from step S3 and stirring to disperse; S5, performing ultrasonic and vacuum degassing treatment, and aging at 4°C for 4 hours. Compared with existing technologies, this invention has the advantages of effectively blocking heat radiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inhibitor technology, specifically relating to a heat radiation blocking composite gel for preventing mine fires and its preparation method. Background Technology

[0002] Coal, as a crucial pillar of the global energy system, remains a primary energy source for many countries. Mine fires have always been a major threat to coal mine safety. Due to the inherent characteristics of the coal mine working environment, heat conduction and convection are relatively low, making thermal radiation the core pathway for high-temperature heat sources to transfer heat to surrounding coal seams, especially those at higher elevations. Traditional fire prevention and extinguishing technologies suffer from high-temperature failure in fire zones dominated by thermal radiation, making it difficult to effectively block thermal radiation. Summary of the Invention

[0003] In order to overcome the shortcomings of existing technologies and solve the technical problems of existing fire prevention and extinguishing technologies such as high-temperature failure and difficulty in effectively blocking heat radiation in high-temperature fire zones dominated by heat radiation, this invention provides a heat radiation blocking composite gel for preventing mine fires and its preparation method.

[0004] The present invention is achieved through the following technical solutions.

[0005] This invention provides a heat radiation blocking composite gel for preventing mine fires, comprising, by weight, 100 parts of ultrapure water, 1-2.5 parts of hydroxypropyl methylcellulose, 30 parts of fly ash, 0-4 parts of sepiolite, and 0-4 parts of expanded graphite.

[0006] Furthermore, by weight, it includes 100 parts of ultrapure water, 1.5 parts of hydroxypropyl methylcellulose, 30 parts of fly ash, 2 parts of sepiolite, and 2 parts of expanded graphite.

[0007] Furthermore, its preparation method includes the following steps: S1. Prepare hydroxypropyl methylcellulose base solution using 100 parts of ultrapure water and 1-2.5 parts of hydroxypropyl methylcellulose; S2. Add the pretreated 0-4 parts of sepiolite to the hydroxypropyl methylcellulose base solution at a rate of 600 r / min and stir to disperse for 15 min. S3. Add the pretreated 30 parts of fly ash to the slurry from step S2 in batches at a rate of 600 r / min and stir and disperse for 15 min. S4. Add the pretreated 0-4 parts of expanded graphite to the slurry from step S3 at a rate of 200 r / min and stir and disperse for 10 min. S5. The slurry from step S4 is ultrasonically treated with a power of 150-200W for 3-5 minutes, then vacuum degassed for 5 minutes, and then placed in a 4℃ environment for static aging for 4 hours to obtain a heat radiation blocking composite gel.

[0008] Furthermore, the preparation of the hydroxypropyl methylcellulose-based solution in step S1 includes: Place 100 parts of ultrapure water in a constant temperature stirring device at a temperature of 20-25℃ and a stirring speed of 800r / min, and add 1-2.5 parts of hydroxypropyl methylcellulose into the constant temperature stirring device using a dispersion sieve. Adjust the speed of the constant temperature stirring device to 600 r / min and stir for 15 min to form a milky white suspension system; Hydroxypropyl methylcellulose base solution was prepared by placing the milky white suspension system at 4°C and refrigerating it for 12 hours.

[0009] Furthermore, the sepiolite pretreatment includes drying the sepiolite in an environment of 80°C for 6 hours, then defiberizing it using a pulverizer and passing it through a 300-mesh sieve.

[0010] Furthermore, the fly ash pretreatment includes drying the fly ash in an environment of 105°C for 4 hours, and then passing it through a 200-mesh sieve after cooling.

[0011] Furthermore, the pretreatment of expanded graphite includes drying the expanded graphite in an environment of 60°C for 2 hours.

[0012] Furthermore, the vacuum degree of the vacuum degassing process in step S5 is -0.08MPa to -0.09MPa.

[0013] The beneficial effects achieved by this invention are: 1. This invention uses hydroxypropyl methylcellulose, fly ash, sepiolite, and expanded graphite to prepare a heat radiation blocking composite gel. The hydrophobic association of hydroxypropyl methylcellulose molecular chains forms a dense cross-linked network. Fly ash particles fill the network to enhance the density and structural strength of the covering layer. Sepiolite fibers are interwoven in the skeleton to form an interwoven support structure at high temperatures, maintaining the integrity of the covering layer and blocking oxygen from diffusing to the coal surface. Expanded graphite expands at high temperatures to form a loose and porous heat-insulating carbon layer, which attenuates the transmission of heat radiation to the coal body, thereby effectively blocking heat radiation. 2. In the thermal radiation blocking composite gel prepared by this invention, the evaporation of water, degradation of the hydroxypropyl methylcellulose backbone, stepwise dehydration and dehydroxylation reaction of sepiolite, decomposition and gasification expansion of expanded graphite intercalating agent, and secondary pyrolysis of carbon layer together constitute a stepwise synergistic endothermic effect, which continuously absorbs heat over a wide temperature range and inhibits the rise in coal temperature.

[0014] Compared with existing technologies, the present invention has the advantages of effectively blocking thermal radiation. Attached Figure Description

[0015] Figure 1 This is a schematic diagram showing the changes in different sepiolite contents over time in Examples 6, 9-12. Figure 2 This is a schematic diagram showing the change of phase transformation temperature (LCST) with the content of sepiolite and expanded graphite in Examples 6, 9-32; Figure 3 This is a schematic diagram showing the change in viscosity with the content of sepiolite and expanded graphite in Examples 6, 9-32; Figure 4 This is a schematic diagram showing the change in gelation time with the content of sepiolite and expanded graphite in Examples 6, 9-32; Figure 5 This is a schematic diagram showing the temperature changes of raw coal and the products prepared in Examples 6, 10, and 17. Figure 6 This is a graph showing the changes in CO generation rate for raw coal and the products prepared in Examples 6, 10, and 17. Figure 7 This is a graph showing the change in heat release rate of raw coal and the products prepared in Examples 6, 10, and 17. Figure 8 This is a graph showing the changes in total heat release of raw coal and the products prepared in Examples 6, 10, and 17. Figure 9 This is a graph showing the changes in total flue gas generated from raw coal and the products prepared in Examples 6, 10, and 17. Figure 10 This is a graph showing the changes in the mass and mass loss rate of raw coal, the products prepared in Examples 6, 10, and 17. Detailed Implementation

[0016] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments.

[0017] Example 1 A hydroxypropyl methylcellulose gel comprising, by weight, 100 parts of ultrapure water and 1 part of hydroxypropyl methylcellulose.

[0018] A method for preparing hydroxypropyl methylcellulose gel includes the following steps: Place 100 parts of ultrapure water in a constant temperature stirring device at a temperature of 20-25℃ and a stirring speed of 800r / min. Pre-stir to form a stable vortex flow field. Add 1 part of hydroxypropyl methylcellulose to the constant temperature stirring device using a dispersing sieve. Control the feeding time to be no less than 10 minutes. This can avoid the phenomenon of agglomeration and coating caused by excessively high local concentration.

[0019] Adjust the speed of the constant temperature stirring device to 600 r / min, stir for 15 min to fully wet and swell the hydroxypropyl methylcellulose particles to form a milky white suspension system, and continue to use intermittent stirring, such as stirring for 5 min and letting stand for 2 min, to promote further deagglomeration of the incompletely hydrated particles.

[0020] A milky white suspension was placed at 4°C and refrigerated for 12 hours to allow the hydroxypropyl methylcellulose molecular chains to fully hydrate and extend, thus preparing a hydroxypropyl methylcellulose-based liquid. Under low-temperature conditions, the hydrophilic groups of hydroxypropyl methylcellulose form stable hydrogen-bonded association structures with water molecules, and the molecular chains gradually transform from a coiled state to a stretched state, thereby constructing a uniform and stable pre-network structure.

[0021] The refrigerated hydroxypropyl methylcellulose base solution was placed back under low-speed stirring at 300 r / min for 10 min to degas, in order to eliminate internal microbubbles and improve the uniformity of the subsequent gel structure. Then, it was vacuum degassed in an environment with a vacuum degree of -0.08 MPa to -0.09 MPa for 5 min, and then placed in an environment of 4℃ for static aging for 4 h to further stabilize the internal hydrogen bonding and hydrophobic association, thus obtaining a transparent and uniform hydroxypropyl methylcellulose gel.

[0022] Example 2 This embodiment is basically the same as Example 1, except that the hydroxypropyl methylcellulose is replaced with 1.5 parts.

[0023] Example 3 This embodiment is basically the same as Embodiment 1, except that the hydroxypropyl methylcellulose is replaced with 2 parts.

[0024] Example 4 This embodiment is basically the same as Embodiment 1, except that the hydroxypropyl methylcellulose is changed to 2.5 parts.

[0025] Example 5 A hydroxypropyl methylcellulose-fly ash gel comprises, by weight, 100 parts of ultrapure water, 1 part of hydroxypropyl methylcellulose and 30 parts of fly ash.

[0026] A method for preparing hydroxypropyl methylcellulose-fly ash gel includes the following steps: Thirty portions of fly ash were pretreated, including drying the fly ash at 105°C for 4 hours to remove surface adsorbed water, and then passing it through a 200-mesh sieve after cooling.

[0027] Place 100 parts of ultrapure water in a constant temperature stirring device at a temperature of 20-25℃ and a stirring speed of 800r / min. Pre-stir to form a stable vortex flow field. Add 1 part of hydroxypropyl methylcellulose to the constant temperature stirring device using a dispersing sieve. Control the feeding time to be no less than 10 minutes. This can avoid the phenomenon of agglomeration and coating caused by excessively high local concentration.

[0028] Adjust the speed of the constant temperature stirring device to 600 r / min, stir for 15 min to fully wet and swell the hydroxypropyl methylcellulose particles to form a milky white suspension system, and continue to use intermittent stirring, such as stirring for 5 min and letting stand for 2 min, to promote further deagglomeration of the incompletely hydrated particles.

[0029] A milky white suspension was placed at 4°C and refrigerated for 12 hours to allow the hydroxypropyl methylcellulose molecular chains to fully hydrate and extend, thus preparing a hydroxypropyl methylcellulose-based liquid. Under low-temperature conditions, the hydrophilic groups of hydroxypropyl methylcellulose form stable hydrogen-bonded association structures with water molecules, and the molecular chains gradually transform from a coiled state to a stretched state, thereby constructing a uniform and stable pre-network structure.

[0030] Thirty parts of pretreated fly ash were added in batches to the hydroxypropyl methylcellulose-based liquid at a feeding rate of 2-3 parts per minute and 600 r / min, and stirred and dispersed for 15 minutes to ensure that the fly ash particles were uniformly embedded in the three-dimensional network structure of hydroxypropyl methylcellulose. The active silica-alumina sites on the surface of the fly ash can form interfacial hydrogen bonds with the hydroxypropyl methylcellulose molecular chains, thereby enhancing the physical cross-linking degree of the composite gel. During the batch addition process, the fly ash particles were uniformly dispersed before the next batch was added to avoid local enrichment of inorganic particles that would lead to system agglomeration.

[0031] After stirring, the gel was placed under a low-speed stirring condition of 300 r / min for 10 min to degas, in order to eliminate internal microbubbles and improve the uniformity of the subsequent gel structure. Then, it was vacuum degassed in an environment with a vacuum degree of -0.08 MPa to -0.09 MPa for 5 min, and then placed in an environment of 4℃ for static aging for 4 h to further stabilize the internal structure, thus obtaining a homogeneous gray hydroxypropyl methylcellulose-fly ash gel.

[0032] Example 6 This embodiment is basically the same as embodiment 5, except that the hydroxypropyl methylcellulose is replaced with 1.5 parts.

[0033] Example 7 This embodiment is basically the same as embodiment 5, except that the hydroxypropyl methylcellulose is replaced with 2 parts.

[0034] Example 8 This embodiment is basically the same as embodiment 5, except that the hydroxypropyl methylcellulose is changed to 2.5 parts.

[0035] Example 9 A hydroxypropyl methylcellulose-sepiolite-fly ash gel comprises, by weight, 100 parts of ultrapure water, 1.5 parts of hydroxypropyl methylcellulose, 30 parts of fly ash and 1 part of sepiolite.

[0036] A method for preparing hydroxypropyl methylcellulose-sepiolite-fly ash gel includes the following steps: Thirty portions of fly ash were pretreated, including drying the fly ash at 105°C for 4 hours to remove surface adsorbed water, and then passing it through a 200-mesh sieve after cooling.

[0037] One part of sepiolite was pretreated by drying it at 80°C for 6 hours to remove free water from the pores of the sepiolite, and then it was defiberized by a pulverizer and passed through a 300-mesh sieve.

[0038] Place 100 parts of ultrapure water in a constant temperature stirring device at a temperature of 20-25℃ and a stirring speed of 800r / min. Pre-stir to form a stable vortex flow field. Add 1.5 parts of hydroxypropyl methylcellulose to the constant temperature stirring device using a dispersion sieve. Control the feeding time to be no less than 10 minutes to avoid local high concentrations that could lead to agglomeration and coating.

[0039] Adjust the speed of the constant temperature stirring device to 600 r / min, stir for 15 min to fully wet and swell the hydroxypropyl methylcellulose particles to form a milky white suspension system, and continue to use intermittent stirring, such as stirring for 5 min and letting stand for 2 min, to promote further deagglomeration of the incompletely hydrated particles.

[0040] A milky white suspension was placed at 4°C and refrigerated for 12 hours to allow the hydroxypropyl methylcellulose molecular chains to fully hydrate and extend, thus preparing a hydroxypropyl methylcellulose-based liquid. Under low-temperature conditions, the hydrophilic groups of hydroxypropyl methylcellulose form stable hydrogen-bonded association structures with water molecules, and the molecular chains gradually transform from a coiled state to a stretched state, thereby constructing a uniform and stable pre-network structure.

[0041] One part of pretreated sepiolite was added to hydroxypropyl methylcellulose base liquid at a rate of 600 r / min and stirred and dispersed for 15 min. Under shearing action, sepiolite fibers gradually defibriled and were evenly dispersed. Hydrogen bonds were formed between the silanol groups on its surface and the hydroxypropyl methylcellulose molecular chains to construct a fiber-reinforced composite network.

[0042] Thirty parts of pretreated fly ash were added in batches to the slurry formed by hydroxypropyl methylcellulose-based liquid and sepiolite at a feeding rate of 2-3 parts per minute and 600 r / min. The mixture was stirred and dispersed for 15 minutes. The fly ash particles gradually filled the gaps in the network formed by the sepiolite fibers and hydroxypropyl methylcellulose, thereby improving the structural density of the gel system. During the batch addition process, the fly ash particles were evenly dispersed before the next batch was added to avoid local enrichment of inorganic particles that would lead to system agglomeration.

[0043] After stirring, the mixture is ultrasonically treated at 150-200W for 3-5 minutes, followed by vacuum degassing for 5 minutes. The vacuum degree of the vacuum degassing is -0.08MPa to -0.09MPa. Ultrasonic treatment further breaks down local agglomerates and improves the uniformity of the system. The mixture is then placed in a 4℃ environment for static aging for 4 hours to allow the sepiolite fibers, fly ash particles and hydroxypropyl methylcellulose network to form a stable synergistic structure, resulting in a hydroxypropyl methylcellulose-sepiolite-fly ash gel with high structural stability.

[0044] Example 10 This embodiment is basically the same as embodiment 9, except that the sepiolite is replaced with 2 parts.

[0045] Example 11 This embodiment is basically the same as embodiment 9, except that the sepiolite is replaced with 3 parts.

[0046] Example 12 This embodiment is basically the same as embodiment 9, except that the sepiolite is changed to 4 parts.

[0047] Example 13 A hydroxypropyl methylcellulose-fly ash-expanded graphite gel comprises, by weight, 100 parts of ultrapure water, 1.5 parts of hydroxypropyl methylcellulose, 30 parts of fly ash and 1 part of expanded graphite.

[0048] A method for preparing hydroxypropyl methylcellulose-fly ash-expanded graphite gel includes the following steps: Thirty portions of fly ash were pretreated, including drying the fly ash at 105°C for 4 hours to remove surface adsorbed water, and then passing it through a 200-mesh sieve after cooling.

[0049] One part of expanded graphite was pretreated by drying it at 60°C for 2 hours to reduce the effect of interlayer adsorbed water on the dispersion stability of the system.

[0050] Place 100 parts of ultrapure water in a constant temperature stirring device at a temperature of 20-25℃ and a stirring speed of 800r / min. Pre-stir to form a stable vortex flow field. Add 1.5 parts of hydroxypropyl methylcellulose to the constant temperature stirring device using a dispersion sieve. Control the feeding time to be no less than 10 minutes to avoid local high concentrations that could lead to agglomeration and coating.

[0051] Adjust the speed of the constant temperature stirring device to 600 r / min, stir for 15 min to fully wet and swell the hydroxypropyl methylcellulose particles to form a milky white suspension system, and continue to use intermittent stirring, such as stirring for 5 min and letting stand for 2 min, to promote further deagglomeration of the incompletely hydrated particles.

[0052] A milky white suspension was placed at 4°C and refrigerated for 12 hours to allow the hydroxypropyl methylcellulose molecular chains to fully hydrate and extend, thus preparing a hydroxypropyl methylcellulose-based liquid. Under low-temperature conditions, the hydrophilic groups of hydroxypropyl methylcellulose form stable hydrogen-bonded association structures with water molecules, and the molecular chains gradually transform from a coiled state to a stretched state, thereby constructing a uniform and stable pre-network structure.

[0053] Thirty parts of pretreated fly ash were added in batches to the hydroxypropyl methylcellulose-based liquid at a feeding rate of 2-3 parts per minute and 600 r / min, and stirred and dispersed for 15 minutes to ensure that the fly ash particles were uniformly embedded in the three-dimensional network structure of hydroxypropyl methylcellulose. The active silica-alumina sites on the surface of the fly ash can form interfacial hydrogen bonds with the hydroxypropyl methylcellulose molecular chains, thereby enhancing the physical cross-linking degree of the composite gel. During the batch addition process, the fly ash particles were uniformly dispersed before the next batch was added to avoid local enrichment of inorganic particles that would lead to system agglomeration.

[0054] One part of pretreated expanded graphite was added to the system formed by hydroxypropyl methylcellulose-based liquid and fly ash at a rate of 200 r / min and stirred for 10 min. The feeding time was controlled to be no less than 8 min to avoid local accumulation of sheet graphite. Stirring for 10 min ensured that the expanded graphite was uniformly dispersed in the composite system, while avoiding high shear damage to its layered structure and subsequent high-temperature expansion performance. The expanded graphite sheets gradually distributed inside the hydroxypropyl methylcellulose-fly ash network, forming a layered barrier structure, and constructing a porous expanded carbon layer during subsequent heating.

[0055] After stirring, vacuum degassing was performed for 5 minutes at a vacuum level of -0.08 MPa to -0.09 MPa to improve the uniformity of the system. The system was then placed in a 4°C environment for static aging for 4 hours to allow the expanded graphite, fly ash particles and hydroxypropyl methylcellulose network to form a stable synergistic structure, resulting in a hydroxypropyl methylcellulose-fly ash-expanded graphite gel with a uniform structure.

[0056] Example 14 This embodiment is basically the same as embodiment 13, except that the expanded graphite is replaced with 2 parts.

[0057] Example 15 This embodiment is basically the same as embodiment 13, except that the expanded graphite is replaced with 3 parts.

[0058] Example 16 This embodiment is basically the same as embodiment 13, except that the expanded graphite is changed to 4 parts.

[0059] Example 17 A heat radiation blocking composite gel for preventing mine fires comprises, by weight, 100 parts of ultrapure water, 1.5 parts of hydroxypropyl methylcellulose (HPMC), 30 parts of fly ash (FA), 2 parts of sepiolite (SPE), and 2 parts of expanded graphite (EG).

[0060] A method for preparing a heat radiation blocking composite gel for preventing mine fires includes the following steps: Thirty portions of fly ash were pretreated, including drying the fly ash at 105°C for 4 hours to remove surface adsorbed water, and then passing it through a 200-mesh sieve after cooling.

[0061] Two portions of sepiolite were pretreated by drying them at 80°C for 6 hours to remove free water from the pores, followed by defiberization using a pulverizer and passing them through a 300-mesh sieve.

[0062] Two portions of expanded graphite were pretreated, including drying the expanded graphite at 60°C for 2 hours to reduce the impact of interlayer adsorbed water on the dispersion stability of the system.

[0063] Place 100 parts of ultrapure water in a constant temperature stirring device at a temperature of 20-25℃ and a stirring speed of 800r / min. Pre-stir to form a stable vortex flow field. Add 1.5 parts of hydroxypropyl methylcellulose to the constant temperature stirring device using a dispersion sieve. Control the feeding time to be no less than 10 minutes to avoid local high concentrations that could lead to agglomeration and coating.

[0064] Adjust the speed of the constant temperature stirring device to 600 r / min, stir for 15 min to fully wet and swell the hydroxypropyl methylcellulose particles to form a milky white suspension system, and continue to use intermittent stirring, such as stirring for 5 min and letting stand for 2 min, to promote further deagglomeration of the incompletely hydrated particles.

[0065] A milky white suspension was placed at 4°C and refrigerated for 12 hours to allow the hydroxypropyl methylcellulose molecular chains to fully hydrate and extend, thus preparing a hydroxypropyl methylcellulose-based liquid. Under low-temperature conditions, the hydrophilic groups of hydroxypropyl methylcellulose form stable hydrogen-bonded association structures with water molecules, and the molecular chains gradually transform from a coiled state to a stretched state, thereby constructing a uniform and stable pre-network structure.

[0066] Two portions of pretreated sepiolite were added to hydroxypropyl methylcellulose base solution at a rate of 600 r / min and stirred for 15 min. The sepiolite fibers gradually defibriled and dispersed uniformly under shearing action, and hydrogen bonds were formed between the silanol groups on the surface and the hydroxypropyl methylcellulose molecular chains to construct a fiber-reinforced composite network.

[0067] Thirty parts of pretreated fly ash were added in batches to the slurry formed by hydroxypropyl methylcellulose-based liquid and sepiolite at a feeding rate of 2-3 parts per minute and 600 r / min. The mixture was stirred and dispersed for 15 minutes. The fly ash particles gradually filled the gaps in the network formed by the sepiolite fibers and hydroxypropyl methylcellulose, thereby improving the structural density of the gel system. During the batch addition process, the fly ash particles were evenly dispersed before the next batch was added to avoid local enrichment of inorganic particles that would lead to system agglomeration.

[0068] Two portions of pretreated expanded graphite were added to a slurry composed of hydroxypropyl methylcellulose-based liquid, sepiolite, and fly ash at a rate of 200 r / min and stirred for 10 min. The addition time was controlled to be no less than 8 min to avoid local accumulation of the flaky graphite. Stirring for 10 min ensured that the expanded graphite was uniformly dispersed in the composite system, while avoiding high shear damage to its layered structure and subsequent high-temperature expansion performance. The expanded graphite flaky layers gradually distributed within the hydroxypropyl methylcellulose-fly ash network, forming a layered barrier structure and constructing a porous expanded carbon layer during subsequent heating.

[0069] After stirring, the mixture is ultrasonically treated at 150-200W for 3-5 minutes, followed by vacuum degassing for 5 minutes at a vacuum level of -0.08MPa to -0.09MPa. Ultrasonic treatment further breaks down localized agglomerates and improves system homogeneity. The mixture is then left to stand at 4℃ for 4 hours to allow a stable multi-scale synergistic composite network structure to form between the hydroxypropyl methylcellulose molecular chains, sepiolite fibers, fly ash particles, and expanded graphite sheets, resulting in a heat-radiation-blocking composite gel. This heat-radiation-blocking composite gel maintains low viscosity flow dynamics at room temperature and undergoes a rapid sol-gel transition upon heating, forming a dense covering layer with heat insulation, oxygen barrier, and heat absorption properties in high-temperature regions.

[0070] Example 18 This embodiment is basically the same as embodiment 17, except that the sepiolite is replaced with 1 part and the expanded graphite is replaced with 1 part.

[0071] Example 19 This embodiment is basically the same as embodiment 17, except that the sepiolite is replaced with 1 part and the expanded graphite is replaced with 2 parts.

[0072] Example 20 This embodiment is basically the same as embodiment 17, except that the sepiolite is replaced with 1 part and the expanded graphite with 3 parts.

[0073] Example 21 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 1 part and the expanded graphite is changed to 4 parts.

[0074] Example 22 This embodiment is basically the same as embodiment 17, except that the sepiolite is replaced with 2 parts and the expanded graphite is replaced with 1 part.

[0075] Example 23 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 2 parts and the expanded graphite is changed to 3 parts.

[0076] Example 24 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 2 parts and the expanded graphite is changed to 4 parts.

[0077] Example 25 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 3 parts and the expanded graphite is changed to 1 part.

[0078] Example 26 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 3 parts and the expanded graphite is changed to 2 parts.

[0079] Example 27 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 3 parts and the expanded graphite is changed to 3 parts.

[0080] Example 28 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 3 parts and the expanded graphite is changed to 4 parts.

[0081] Example 29 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 4 parts and the expanded graphite is changed to 1 part.

[0082] Example 30 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 4 parts and the expanded graphite is changed to 2 parts.

[0083] Example 31 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 4 parts and the expanded graphite is changed to 3 parts.

[0084] Example 32 This embodiment is basically the same as embodiment 17, except that the sepiolite is changed to 4 parts and the expanded graphite is changed to 4 parts.

[0085] The products prepared in Examples 1-32 were tested for gel time, phase transition temperature, viscosity, water retention and inhibition properties.

[0086] The gel time test mainly involves placing the products prepared in Examples 1-32 into 18mm×180mm test tubes, placing the test tubes in a 90℃ constant temperature water bath, timing and observing the changes in the gel state. Timing is stopped when the solution no longer flows downwards after the test tube is rotated 180°. The time elapsed at this point is the gel time.

[0087] The phase transition temperature test mainly involves placing a test tube containing approximately 4 mL of the product prepared in Examples 1-32 into a constant temperature water bath and heating it for 15 minutes. After removing it, the tube is inverted 180° to observe the flow of the solution. If the solution no longer flows downwards, the current water bath temperature is the phase transition temperature of the gel; if flow still occurs, the water bath temperature is increased in a 1°C gradient, and the heating and observation are repeated until the phase transition temperature is found.

[0088] Viscosity testing mainly involved testing the products prepared in Examples 1-32 using an NDJ-5Spro rotational viscometer.

[0089] The water retention rate test mainly involves placing the products prepared in Examples 1-32 into a crucible and placing it in a vacuum drying oven at 100°C. The crucible is removed and weighed every 1 hour until the mass of two consecutive weighings is constant, at which point the water retention rate can be calculated.

[0090] The flame retardancy performance test was mainly conducted using a high-temperature heat source quantitative thermal radiation experimental system. The container dimensions were approximately 940mm × 940mm × 6mm, and the amount of coal sample used was 25g. The amount of product prepared in Examples 1-32 was 50g. The coal sample and the prepared product were laid out in the container from bottom to top. The thermocouple was located at the geometric center of the coal sample to monitor the change in coal temperature during thermal radiation. At the same time, parameters such as CO, flue gas, mass, and coal temperature changes during coal oxidation combustion under different thermal radiation fluxes were collected.

[0091] Table 1. Phase transition temperatures of the products prepared in Examples 1-8 Phase transition temperature (°C) Unable to form glue 73 69 65 Unable to form glue 69 66 46 Table 1 shows the phase transition temperatures of the products prepared in Examples 1-8. As can be seen from Table 1, no phase transition temperature was observed in Examples 1 and 5. This is because in Examples 1 and 5, hydroxypropyl methylcellulose was present in a single part. At this concentration, the molecular chains of hydroxypropyl methylcellulose had a large inter-chain spacing, making it difficult for the hydrophobic groups to effectively associate and form a continuous three-dimensional gel network. After the molecular chains contracted and aggregated, they could not form a homogeneous gel and ultimately precipitated in a solid-liquid stratification manner. In Examples 1-4, without the addition of fly ash, the phase transition temperature decreased with increasing hydroxypropyl methylcellulose concentration. In Examples 5-8, after the addition of fly ash, the overall phase transition temperature decreased further, with a more significant decrease at high hydroxypropyl methylcellulose concentrations. The decrease in phase transition temperature with increasing hydroxypropyl methylcellulose concentration is due to the simultaneous presence of hydrophilic hydroxypropyl groups and hydrophobic methoxy groups on the hydroxypropyl methylcellulose molecular chains. At lower concentrations, hydrophilic interaction is dominant, requiring higher temperatures to break hydrogen bonds and initiate hydrophobic association. As the concentration increases, the content of hydrophobic groups increases, the hydrophobic interaction strengthens, the heat required for phase transition decreases, and the phase transition temperature decreases accordingly. The addition of fly ash further reduces the phase transition temperature. This is attributed to the fact that the active sites on the surface of fly ash particles compete with water molecules for hydrogen bonds, promoting the dehydration of hydrophobic groups in hydroxypropyl methylcellulose. Simultaneously, fly ash particles act as physical cross-linking points, enhancing hydrophobic association between macromolecules. The promoting effect of fly ash is stronger with higher concentrations of hydroxypropyl methylcellulose, resulting in a more significant decrease in phase transition temperature.

[0092] Table 2. Gel timeline of products prepared in Examples 1-8 Gel time (s) Unable to form glue 235 125 80 Unable to form glue 80 50 5 Table 2 shows the gelation times of the products prepared in Examples 1-8. A shorter gelation time indicates that the material can rapidly undergo a sol-gel transition near the heat source under thermal radiation, forming a viscoelastic coating layer that provides in-situ coverage and isolation of the heat radiation source. Table 2 shows that the gelation time decreases with increasing hydroxypropyl methylcellulose concentration. In Examples 5-8, the addition of fly ash further shortens the overall gelation time. This shortening is attributed to the increased concentration lowering the phase transition temperature and increasing the temperature difference with the test temperature, thus accelerating the hydrophobic association process. Fly ash particles, acting as physical crosslinking points, further promote the association of hydroxypropyl methylcellulose molecular chains, accelerating gel network formation. This promoting effect is more significant at high hydroxypropyl methylcellulose concentrations, resulting in a greater decrease in gel time.

[0093] Table 3 Viscosity table of the products prepared in Examples 1-8 Viscosity (mPa·s) 241 1133 4037 10643 406 1900 7124 20733 Table 3 shows the viscosity of the products prepared in Examples 1-8. Lower viscosity indicates a low-viscosity sol state, ensuring good flowability and low transport resistance, facilitating long-distance pumping to the underground fire zone via pipelines. Table 3 shows that in Examples 1-4 without fly ash, the viscosity increased with increasing hydroxypropyl methylcellulose concentration. In Examples 5-8, with the addition of fly ash, the viscosity at the corresponding concentration increased significantly, and the thickening effect increased with increasing hydroxypropyl methylcellulose concentration. The viscosity increase is mainly due to the intensified entanglement of hydroxypropyl methylcellulose molecular chains at high concentrations, forming a denser three-dimensional network structure, increasing the system's flow resistance. The addition of fly ash further increases the viscosity, attributed to the fly ash particles acting as inorganic fillers dispersed in the network, increasing internal friction resistance, while its surface-active groups form hydrogen bonds with hydroxypropyl methylcellulose, enhancing the network structure.

[0094] Tables 1 to 3 show that the addition of fly ash further reduced the phase transition temperature, increased the viscosity, shortened the gelation time, and solved the solid-liquid separation problem of the system at a concentration of 1.5 parts hydroxypropyl methylcellulose.

[0095] Figure 1 The diagrams shown illustrate the changes in sepiolite content over time in Examples 6, 9-12. It can be seen that the water retention rate initially decreases rapidly and then gradually stabilizes over time. With increasing sepiolite content, the gel dehydration rate gradually slows down, and the equilibrium water retention rate gradually increases.

[0096] Figure 2 The diagram illustrates the changes in phase transition temperature (LCST) with the content of sepiolite and expanded graphite in Examples 6, 9-32. It shows that the LCST decreases with increasing sepiolite and expanded graphite content, with a greater decrease when both are co-mixed. When both sepiolite and expanded graphite are at 4%, the LCST drops to 56°C. The decrease in LCST is due to the formation of hydrogen bonds between the active silanol groups on the surface of sepiolite fibers and hydroxypropyl methylcellulose, promoting the dehydration of hydrophobic groups. The residual polar groups from the expanded graphite intercalator also compete for water molecules. The combined effect of these two factors allows the hydrophobic association of hydroxypropyl methylcellulose to occur at a lower temperature. The intercalator is an important component in the preparation of expanded graphite. It is chemically embedded between graphite layers and rapidly decomposes upon heating to generate gas, driving a dramatic expansion of the graphite volume to form a loose, porous, heat-insulating carbon layer. This expanded carbon layer effectively attenuates the transfer of heat radiation to the coal and blocks oxygen, thus synergistically performing fire prevention and extinguishing functions with other components in the gel. Sepiolite has a stronger effect on lowering the phase transition temperature than expanded graphite, which is attributed to the fact that the fibrous structure of sepiolite provides more physical cross-linking points.

[0097] Figure 3The diagram illustrates the viscosity variations with increasing sepiolite and expanded graphite content in Examples 6, 9-32. It shows that the viscosity continuously increases with increasing sepiolite and expanded graphite content. Sepiolite exhibits a stronger thickening effect than expanded graphite, which is related to the physical entanglement and hydrogen bond cross-linking formed by the fibrous structure of sepiolite within the hydroxypropyl methylcellulose network, enhancing network density. The thickening effect of expanded graphite mainly comes from the filling effect of the lamellar particles, contributing less to the viscosity.

[0098] Figure 4 The diagram illustrates the changes in gel time with the content of sepiolite and expanded graphite in Examples 6, 9-32. It shows that the gel time decreases with increasing sepiolite and expanded graphite content. Sepiolite has a stronger effect on shortening the gel time than expanded graphite, which is related to sepiolite acting as a physical crosslinking point to accelerate the hydrophobic association of hydroxypropyl methylcellulose molecular chains. Expanded graphite has a relatively smaller shortening effect, but its layered structure provides certain nucleation sites. The gel time decrease is greatest when both are co-doped, reflecting the synergistic effect of sepiolite and expanded graphite in promoting gel network formation.

[0099] from Figures 1 to 4 As can be seen, sepiolite plays a role in reducing phase transition temperature, increasing viscosity, and shortening gel time through physical cross-linking of its fiber structure and hydrogen bonding of its surface hydroxyl groups; expanded graphite mainly plays a role through lamellar filling and the contribution of residual groups in the intercalating agent. When the two are combined, they exhibit a synergistic effect and have superior overall performance.

[0100] Figure 5 The diagram shows the temperature changes of the products prepared from raw coal in Examples 6, 10, and 17. Temperature is the most direct indicator for evaluating the performance of fire-retardant materials. A slower temperature rise and a lower final equilibrium temperature indicate a better effect of the gel in attenuating thermal radiation and inhibiting the coal-oxygen reaction. Figure 5 It can be seen that the temperature of the raw coal rises rapidly in the initial stage, reaching a peak of about 650℃ at about 800s, and then stabilizes at 620-630℃. The heating rate of the coal sample in Example 6 slows down, and the temperature is about 620℃ at 2000s. The heating process in Example 10 is gradual, and the temperature is about 600℃ at 2000s. The coal sample in Example 17 has the slowest heating rate, and the temperature is about 380℃ at 2000s, which is the lowest value among all groups. The heat insulation and cooling effect is the most prominent. This is related to the synergistic barrier effect formed by the filling and reinforcement of fly ash particles, the interwoven support of sepiolite fibers, and the high-temperature expansion insulation of expanded graphite.

[0101] Figure 6 The graph shows the variation in CO generation rate for raw coal and the products prepared in Examples 6, 10, and 17. The variation in CO generation rate is positively correlated with the intensity of the coal-oxygen reaction. Figure 6As can be seen, the peak CO generation rate in Example 6 decreased to approximately 0.0016 g·s⁻¹. -1 Example 10 is similar to Example 6, with a peak CO formation rate of approximately 0.0017 g·s⁻¹. -1 Similarly, the CO generation rate remained at a low level, and both gel systems effectively inhibited the coal oxidation process and reduced the CO generation intensity. In Example 17, the CO generation rate remained at a minimum throughout, with a peak value of only about 0.0008 g·s⁻¹ at 2000 s. -1 This is because the expanded graphite high-temperature expansion thickens the gel coating layer, which, together with fly ash and sepiolite, forms a continuous and stable physical barrier, continuously blocking the contact between oxygen and coal, suppressing the coal-oxygen reaction to the greatest extent, and significantly reducing the carbon monoxide generation rate.

[0102] Figure 7 The graph shows the change in heat release rate for raw coal and the products prepared in Examples 6, 10, and 17. A higher peak heat release rate indicates a more intense coal-oxygen reaction and a greater risk of fire spread. It can be seen that the heat release rate of raw coal rises rapidly at approximately 200 s and reaches a peak of 19 kW·m² at 500 s. -2 The coal-oxygen reaction starts early and has a high instantaneous reaction intensity. In Example 6, the peak value decreased to 14 kW·m³. -2 Furthermore, the peak time was delayed to 1400 s, indicating that the gel encapsulation effect reduced the coal-oxygen contact rate. In Example 10, the peak value of the covered coal sample decreased to 13 kW·m. -2 Furthermore, the peak time was delayed to 1800 s, with sepiolite enhancing gel stability and slowing down the oxidation reaction process. Example 17 showed a low and gradual heat release rate throughout the coal sample, with a peak value of only 7 kW·m³ within 2000 s. -2 This significantly weakens the instantaneous reaction intensity of coal and oxygen.

[0103] Figure 8 The graph shows the change in total heat release of raw coal and the products prepared in Examples 6, 10, and 17. It can be seen that the total heat release of raw coal accumulates rapidly over time, reaching 34 MJ·m³ at 2000 s. -2 The coal-oxygen reaction was complete, and the total oxygen consumption was the highest. In Example 6, the total heat release decreased to 16 MJ·m at 2000 s. -2 The gel initially blocks the oxygen transport pathway and reduces the total reaction amount. In Example 10, the cumulative exothermic heat was further reduced to 14 MJ·m⁻¹. -2 The improved gel structure integrity further limits the degree of oxidation reaction. Example 17 showed a total heat release of only 5 MJ·m³ at 2000 s. -2 The synergistic barrier effect maximizes the suppression of the total oxygen consumption and total heat release accumulation in the coal-oxygen reaction.

[0104] Figure 9The graph shows the changes in total flue gas generation for raw coal, products prepared in Examples 6, 10, and 17. The flue gas mainly originates from volatiles generated during coal pyrolysis, such as polycyclic aromatic hydrocarbons (PAHs) and phenols. A higher total flue gas generation indicates more complete coal pyrolysis and more intense oxidation. The total flue gas generation for raw coal accumulates rapidly, reaching its highest value at 2000 s, indicating complete pyrolysis and oxidation of the coal driven by thermal radiation, resulting in the largest total release of gaseous products. Example 6 shows a significant reduction in total flue gas generation for the coal sample covered, as the gel initially blocks the diffusion of oxygen and volatiles, reducing the total generation of pyrolysis products. Example 10 shows a slower increase in total flue gas generation for the coal sample covered, with the lowest cumulative value at 2000 s. Sepiolite, with its high specific surface area and fibrous structure, enhances the gel's sealing effect and adsorbs flue gas components, resulting in the best long-term smoke suppression effect. Example 17 also shows a low total flue gas generation for the coal sample covered. The high-temperature expansion of expanded graphite thickens the covering layer, enhancing the thermal insulation effect, but the expansion process slightly weakens the gel's density, making the flue gas suppression effect slightly weaker than in Example 10.

[0105] Figure 10 The graphs show the changes in mass and mass loss rate of raw coal, the products prepared in Examples 6, 10, and 17. The initial mass loss curves reflect moisture evaporation. Coal samples treated with gels that have good water retention experience slower initial mass loss, which helps prolong the endothermic cooling time. Higher residual mass of the coal sample covered by the gel indicates that the gel effectively inhibits coal pyrolysis and oxidation, while maintaining its structural integrity at high temperatures. The mass loss curves are similar, with mass loss rates ranging from 18% to 20%. With continued thermal radiation, differences in mass loss gradually become apparent among the groups. Example 6 shows a faster mass decrease, Example 10 shows a more gradual mass loss, and Example 17 shows the smallest mass decrease due to the gel.

[0106] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, modifications can still be made to the embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A heat radiation blocking composite gel for preventing mine fires, characterized in that: By weight, it includes 100 parts ultrapure water, 1-2.5 parts hydroxypropyl methylcellulose, 30 parts fly ash, 0-4 parts sepiolite, and 0-4 parts expanded graphite.

2. The heat radiation blocking composite gel for preventing mine fires according to claim 1, characterized in that: By weight, it includes 100 parts ultrapure water, 1.5 parts hydroxypropyl methylcellulose, 30 parts fly ash, 2 parts sepiolite, and 2 parts expanded graphite.

3. A method for preparing a heat radiation blocking composite gel for preventing mine fires, characterized in that: The heat radiation blocking composite gel for preventing mine fires according to claim 1 comprises the following steps: S1. Prepare hydroxypropyl methylcellulose base solution using 100 parts of ultrapure water and 1-2.5 parts of hydroxypropyl methylcellulose; S2. Add the pretreated 0-4 parts of sepiolite to the hydroxypropyl methylcellulose base solution at a rate of 600 r / min and stir to disperse for 15 min. S3. Add the pretreated 30 parts of fly ash to the slurry from step S2 in batches at a rate of 600 r / min and stir and disperse for 15 min. S4. Add the pretreated 0-4 parts of expanded graphite to the slurry from step S3 at a rate of 200 r / min and stir and disperse for 10 min. S5. The slurry from step S4 is ultrasonically treated with a power of 150-200W for 3-5 minutes, then vacuum degassed for 5 minutes, and then placed in a 4℃ environment for static aging for 4 hours to obtain a heat radiation blocking composite gel.

4. The preparation method of a heat radiation blocking composite gel for preventing mine fires according to claim 3, characterized in that: The preparation of the hydroxypropyl methylcellulose-based solution in step S1 includes: Place 100 parts of ultrapure water in a constant temperature stirring device at a temperature of 20-25℃ and a stirring speed of 800r / min, and add 1-2.5 parts of hydroxypropyl methylcellulose into the constant temperature stirring device using a dispersion sieve. Adjust the speed of the constant temperature stirring device to 600 r / min and stir for 15 min to form a milky white suspension system; Hydroxypropyl methylcellulose base solution was prepared by placing the milky white suspension system at 4°C and refrigerating it for 12 hours.

5. The preparation method of a heat radiation blocking composite gel for preventing mine fires according to claim 3, characterized in that: The sepiolite pretreatment includes drying the sepiolite in an 80°C environment for 6 hours, then defiberizing it using a pulverizer and passing it through a 300-mesh sieve.

6. The method for preparing a heat radiation blocking composite gel for preventing mine fires according to claim 3, characterized in that: The fly ash pretreatment includes drying the fly ash at 105°C for 4 hours, and then passing it through a 200-mesh sieve after cooling.

7. The preparation method of a heat radiation blocking composite gel for preventing mine fires according to claim 3, characterized in that: The pretreatment of expanded graphite includes drying the expanded graphite in an environment of 60°C for 2 hours.

8. The preparation method of a heat radiation blocking composite gel for preventing mine fires according to claim 3, characterized in that: The vacuum degree of the vacuum degassing process in step S5 is -0.08MPa to -0.09MPa.